2013
DOI: 10.1371/journal.pone.0076865
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Predicting Gene Expression Changes in Colonic Mucosa of Western Diet Fed Mlh1+/- Mice

Abstract: Colorectal cancer (CRC) is the second most common cause of cancer-related deaths in the Western world and interactions between genetic and environmental factors, including diet, are suggested to play a critical role in its etiology. We conducted a long-term feeding experiment in the mouse to address gene expression and methylation changes arising in histologically normal colonic mucosa as putative cancer-predisposing events available for early detection. The expression of 94 growth-regulatory genes previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…LS mutation carriers are enrolled in lifelong colonoscopy surveillance with 2–3-year intervals [ 10 ], and we took advantage of the regular surveillance to obtain consecutive specimens. Furthermore, a previous mouse study implicated a number of candidate genes in association with MLH1 mutation and diet [ 11 ], prompting us to evaluate the respective genes as methylation targets in human LS.…”
Section: Introductionmentioning
confidence: 99%
“…LS mutation carriers are enrolled in lifelong colonoscopy surveillance with 2–3-year intervals [ 10 ], and we took advantage of the regular surveillance to obtain consecutive specimens. Furthermore, a previous mouse study implicated a number of candidate genes in association with MLH1 mutation and diet [ 11 ], prompting us to evaluate the respective genes as methylation targets in human LS.…”
Section: Introductionmentioning
confidence: 99%
“…As we used targeted approach to test the promoter methylation, we cannot negate the possibility of methylation of other CpG sites of the Mlh1 promoter region of Mlh1 +/+ allele leading to tissue-specific MLH1 depletion. Additionally, heterozygosity of Mlh1 is known to provoke promoter methylation and as consequence lower expression of multiple tumor suppressor genes in normal GI tract affecting crucial signaling pathways[25]. It is likely, that the lower tissue-specific Mlh1 expression we observed is consequence of altered signaling pathways in Mlh1 +/intestine.…”
mentioning
confidence: 82%
“…Genotyping PCR was performed using Platinum green hot start PCR master mix (Invitrogen, Carlsbad, CA). Lysis buffer components, PCR program and primers [25] used for genotyping are listed in Supplementary table 1. In total 58 mice (39 males and 19 females) were used in this study, the number of mice for each experiment along with the genotype and the age is indicated in the respective figures in the results section.…”
Section: Mice and Genotypingmentioning
confidence: 99%
“…No significant interindividual differences were found within the groups. Details of the genotyping procedure, as well as PCR primers and cycling conditions for Mad2, endogenous Spo11, the Tg(Xmr-Spo11β B ) transgene and Mlh1 alleles have been published previously (Baudat et al, 2000;Dobles et al, 2000;Kauppi et al, 2011;Pussila et al, 2013) and are listed in the supplementary Materials and Methods. All applicable national and institutional guidelines (Animal Experiment Board in Finland and Laboratory Animal Centre of the University of Helsinki, respectively) for the care and use of animals were followed.…”
Section: Mlh1mentioning
confidence: 99%